The Effect of Fibrinogen Concentration on Susceptibility of Clots to in vitro Clot Lysis with Plasmin - Freiman, A. H; Cliffton, E. E (Thrombosis and Haemostasis, 1958)
The effect of fibrinogen(fibrin) concentration on the degree of clot lysis has been is shown. These experiments demonstrate: (1) A direct correlation between degree of clot lysis and liberation of radioactive breakdown products, (2) that increasing concentrations of fibrinogen result in decreasing lysis of the clot by a standard fibrinolysin solution, (3) that lysis occurs more rapidly at pH 7.4 than at pH 7.6 and 7.8, (4) that increase in surface area results in increased lysis and (5) that increasing concentration of plasmin results in increased lysis of the clot.